Privacy protection on Vehicular Ad hoc NETworks. (24th June 2011) - Hwang, Ren-Junn; Hsiao, Yu-Kai; Hwang, Cheng-Yang
Vehicular Ad hoc NETwork (VANET) provides traffic safety and efficient traffic management by taking advantage of messages that are quickly interchanged among vehicles and some infrastructures. The integrity and non-repudiation of messages and vehicle privacy in VANET are quite critical. Pseudonym technology is a practical strategy to ensure these three properties. However, the functionalities and performance of previous related works cannot satisfy the requirements of VANET. This paper proposes a secure message-broadcasting method based on Identity-Based Encryption (IBE) in VANET. This work protects driver/vehicle privacy and track. The method also provides authentication, integrity, non-repudiation, confidentiality, forward secrecy, anonymity, untraceability and responsibility to satisfy the security requirements of VANET communication.